Preparation and Evaluation of a Therapeutic Ointment Using Beehive Derivatives - Drif ,Abdelhak; Rezgui, Asma (Université of eloued جامعة الوادي, 2025)
Natural therapeutic alternatives have become a growing area of interest in recent years, yet the y remain a subject of debate within the medical and scientific communities. This controversy is largely due to the lack of rigorous scientific studies confirming their efficacy and safety. Contributing factors include their potential competition with conve ntional pharmaceutical industries, the shortage of validated research that facilitates scientific advancement, and the ease of public access, which may lead to unsupervised use and unintended health consequences. This study aims to formulate a 100% natural therapeutic ointment using beehive derivatives, primarily beeswax, blended with natural oils ( olive oil, clove oil , Artemisiaoil , and rosemary oil ). Beeswax was obtained from a modern apiary in Guemar, and olive oil from a local press. Essential oils were extracted through hydrodistillation using a Clevenger apparatus. Characterization of the three essential oils and the prepared ointment was performed using Fourier transform infrared spectroscopy (FTIR) to observe the formation of new chemical bonds after blending. In the experimental phase, 100 grams of beeswax were dissolved in 600 mL of olive oil. Three samples of 10 grams each were prepared by adding 0.05 grams of Indigofera tinctoria (natural blue dye) to each, followed by varying concentrations of th e three essential oils (10 µL, 15 µL, and 20 µL, respectively). The biological activity was assessed against Gram positive bacteria Staphylococcus aureus ), Gram negative bacteria ( Escherichia coli ), and certain fungal strains using the agar well diffusion method. The results showed notable antibacterial activity against Gram positive bacteria and antifungal activity, while activity against Gram negative bacteria was limited. These findings open promising prospects for the development and use of this ointme nt as a natural remedy for skin allergies and infections of bacterial, fungal, or potentially viral origin. تُعدّ البدائل العلاجية الطبيعية مجا ا لً متنامي الًهتمام في السنوات الأخيرة، إلً أنها لً تزال محل جدل في الأوساط الطبية والعلمية، ويرجع ذلك أسا ا سا إلى نقص الدراسات العلمية الدقيقة التي تثبت فعاليتها وسلامتها. ومن أبرز العوامل المؤدية إلى هذا الجدل منافستها المحتملة لصناعة الأدوية التقليدية، وغياب الأبحاث المعمّقة التي تسهم في تسهيل التقدم العلمي، بالإضافة إلى سهولة الحصول عليها من قِبل العامة دون إشراف طبي، مما قد يؤدي إلى استخدامها العشوائي وما يترتب على ذلك من مضاعفات صحية غير محسوبة. تهدف هذه الدراسة إلى تحضير مرهم علاجي طبيعي 100 % باستخدام مشتقات خلية النحل، وعلى رأسها شمع النحل، ممزو ا جا بمجموعة من الزيوت الطبيعية )زيت الزيتون، وزيت القرنفل، وزيت الشيح، وزيت إكليل الجبل(. تم الحصول على شمع النحل من منحلة حديثة بمنطقة قمار، أما زيت الزيتون فتم استخراجه من معصرة تقليدية محلية. كما تم استخلاص الزيوت الأساسية للنباتات الثلاثة عبر التقطير بالماء المقطر باستخدام جهاز كليفنجر. وتم تشخيص هذه الزيوت الأساسية والمرهم المحضر باستخدام تقنية التحليل الطيفي بالأشعة تحت الحمراء (FTIR) بهدف الكشف عن تكوّن روابط كيميائية جديدة بعد المزج. في الجانب التطبيقي، تم إذابة 100 غرام من شمع النحل في 600 مل من زيت الزيتون، ثم قمنا بتحضير ثلاث عينات بوزن 10 غرام لكل منها، أضيف إليها 0.05 غرام من النيلة الزرقاء، بالإضافة إلى تراكيز مختلفة من الزيوت الأساسية ) 10 ميكرولتر، 15 ميكرولتر، و 20 ميكرولتر على التوالي(. وقد تم تقييم النشاط الحيوي لهذه العينات ضد بكتيريا موجبة الغرام (Staphylococcus ، وسالبة الغرام (Escherichia ، وبعض السلالًت الفطرية باستخدام طريقة الًنتشار في آبار الآغار. أظهرت النتائج فعالية واضحة ضد البكتيريا موجبة الغرام والفطريات، في حين كانت الفعالية محدودة ضد البكتيريا سالبة الغرام. تظهر هذه النتائج آفاقاا واعدة لًستخدام هذا المرهم كعلاج طبيعي محتمل لأمراض الجلد المرتبطة بالعدوى
Thesis with the master degree in chemistry
Keywords: Rosemary essential oil; Artemisia essential oil; Clove essential oil; Beeswax; Olive oil; Indigofera tinctoria; FTIR; Bioactivity.; زيت إكليل الجبل، زيت الشيح، زيت القرنفل، شمع النحل، زيت الزيتون، النيلة الزرقاء،النشاط